An analytical study of the Chinese Belt and Road Initiative (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The Chinese Belt and Road Initiative is a global development initiative that links China with the world in ways and paths of trade and political exchange, and thus works to draw new alliances and create a new pattern in relations between major countries.The aim of the research is to study the importance and objectives of the initiative, its requirements and the challenges it faces, in addition to analyzing the impact of the initiative on the global economy and global trade.The research reached several results, the most important of which is that the initiative represents China's soft power based on mutual partnership within the framework of a new international cooperation, which works to reshape the global economy and changes global trade paths, thus showing China as an effective international power that raises the concerns of regional and international powers.